Abdominal effusion in a dog - Meindel, Mandy; Pohlman, Lisa M. (My University, 2013)
A 2-year-old, spayed toy poodle mix presented with a distended abdomen. The dog had been seen by the referring veterinarian for a 2-month history of intermittent vomiting. Diagnostic testing (eg, CBC, serum biochemistry profile, radiography) was inconclusive; exploratory laparotomy revealed no significant findings. Biopsies were not performed. Progressive abdominal distention became apparent in the 2 weeks following surgery, and the patient was referred to local specialists.
Keywords: Dog; Distended abdomen; Abdominal effusion; Bile peritonitis; Abdominal fluid analysis